1975
DOI: 10.1172/jci108204
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic organic anion uptake in the rat.

Abstract: A B S T R A CT(a) hepatic uptake determined by direct tissue measurement could be accurately estimated from the plasma disappearance data; (b) saturation of hepatic uptake with increasing dose was readily demonstrated for each of these three organic anions, and in each instance a plot of V versus dose took the form of a rectangular hyperbola analyzable in terms of Michaelis-Menten kinetics; (c) for BR, the saturable uptake process showed a V.a. more than 100 times the normal net transfer rate from plasma to bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
135
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(143 citation statements)
references
References 35 publications
8
135
0
Order By: Relevance
“…These changes in the way in which the liver handles BSP are qualitatively similar to those found previously with ICG (Bowmer et al, 1982a;Yates etal., 1983a,b,c). This is not surprising because there is evidence to suggest that both dyes share the same pathway for hepatic uptake (Scharschmidt et al, 1975;Schwenk et al, 1976).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These changes in the way in which the liver handles BSP are qualitatively similar to those found previously with ICG (Bowmer et al, 1982a;Yates etal., 1983a,b,c). This is not surprising because there is evidence to suggest that both dyes share the same pathway for hepatic uptake (Scharschmidt et al, 1975;Schwenk et al, 1976).…”
Section: Discussionmentioning
confidence: 95%
“…Evidence for this comes largely from studies of competition for transport between pairs of substances. These studies have revealed a number of different routes for organic anions (Alpert et al, 1969;Scharschmidt et al, 1975;Schwenk et al, 1976), cations (Solomon & Schanker, 1963) and uncharged molecules (Kupferberg & Schanker, 1968;Klassen, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…The hepatocyte serves as a major site of organic anion clearance from the circulation (Scharschmidt et al, 1975;Wolkoff, 2012). Many of these compounds are poorly soluble in aqueous solution, and circulate bound to proteins such as albumin (Wolkoff et al, 1987;Choi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang, Strong, Qiu, Lesko, & Huang, 2006;. OATPs were identified on their basis to transport BSP, a substrate which was thought to be transported (in part) by a postulated bilirubin transport system (Clarenburg & Kao, 1973;Scharschmidt, et al, 1975). Many years after their identification it was indeed demonstrated that hOATP1B1 and hOATP1B3 could mediate bilirubin transport (Briz, Serrano, MacIas, Gonzalez-Gallego, & Marin, 2003;Cui, Konig, Leier, Buchholz, & Keppler, 2001).…”
Section: Introductionmentioning
confidence: 99%